2009
DOI: 10.1007/s00432-009-0559-7
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of small breast epithelial mucin mRNA as a marker for bone marrow micrometastasis in breast cancer: a pilot study

Abstract: SBEM might represent a suitable marker for molecular detection of ITCs in BM in breast cancer patients. Analysis of prognostic value for SBEM mRNA-based assay should take into account the heterogeneity and different molecular subtypes of breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…In our study, increased miR-21 level was found in 90.6% of tumors, consistently with previous studies investigating patients with colon (25,27,39), gastric (21,39,45,46) and pancreatic (22,23,29) adenocarcinomas. However, we did not find any significant associations between miR-21 level and the clinical and pathologic characteristics, in line with recently reported results (47).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our study, increased miR-21 level was found in 90.6% of tumors, consistently with previous studies investigating patients with colon (25,27,39), gastric (21,39,45,46) and pancreatic (22,23,29) adenocarcinomas. However, we did not find any significant associations between miR-21 level and the clinical and pathologic characteristics, in line with recently reported results (47).…”
Section: Discussionsupporting
confidence: 93%
“…Immunocytochemistry (ICC) was performed as described previously (27) using the Vectastain ABC-AP kit (Vector), according to the manufacturer's instructions. Slides (5x10 5 BM MNCs) were incubated with the anti-cytokeratin (CK) monoclonal antibodies AE1/AE3 (Dako).…”
Section: Methodsmentioning
confidence: 99%
“…7, 8, 9, 10 Its limited normal tissue expression also renders MUCL1 an attractive tumor-associated antigen for targeted therapy of breast cancers. Despite our understanding of the expression of MUCL1 in breast cancer, the cellular localization of the MUCL1 protein has remained largely unstudied, which will have a major impact on drug developmentability.…”
Section: Introductionmentioning
confidence: 99%
“…SBEM is identified as a putative breast-specific gene and considered to be a promising breast specific marker [9]. Although published studies have suggested that SBEM might represent a suitable marker for molecular detection of isolated tumor cells in bone marrow and targeting bone marrow micrometastasis in breast cancer patients [10,11], thus far, there has been no report on whether the expression of SBEM is a predictor for hematogenous micrometastasis and response to neoadjuvant chemotherapy in breast cancer.…”
Section: Introductionmentioning
confidence: 99%